The postwar African American novel : protest and discontent, 1945-1950 - Brown, Stephanie, 1970- (Margaret Walker Alexander series in African American studies., 2011)
Americans in the World War II era bought the novels of African American writers in unprecedented numbers. However, the names on the books were less well-known ones such as Frank Yerby, Chester Himes, William Gardner Smith, and J. Saunders Redding. This book recovers the work of these innovative novelists, overturning conventional wisdom about the writers of the period and the trajectory of African American literary history. The book also questions the assumptions about the relations between race and genre that have obscured the importance of these once-influential creators.